profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

Упростите выражение : tg t * cos (-t) +sin (pi + t ) =

  1. Ответ
    Ответ дан Соловьёва Лариса
    tg t * cos ( - t ) + sin ( pi + t ) = tg t * cos ( - t ) + ( - sin t ) = tg t * cos ( - t ) - sin t = sin t / cos t * cos ( - t ) - sin t = sin t / cos t * cos t - sin t = sin t / 1 * 1 - sin t = sin t / 1 - sin t = sin t - sin t = sin t * ( 1 - 1 ) = sin t *0 = 0 * sin t = 0 ;
    В итоге получили, tg t * cos ( - t ) + sin ( pi + t ) = 0 ;
    Ответ: tg t * cos ( - t ) + sin ( pi + t ) = 0.
    0